Understanding the GERD Barrier. Issue 6 (July 2021) - Dunn, Colin P.; Wu, Jessica; Gallagher, Shea P.; Putnam, Luke R.; Bildzukewicz, Nikolai A.; Lipham, John C.
Abstract : Gastroesophageal reflux disease (GERD) is steadily increasing in incidence and now affects 18% to 28% of the population in the United States. A thorough understanding of the pathophysiology underlying this disease is necessary to improve the current standard of care. Most GERD pathophysiology models focus on the lower esophageal sphincter (LES) as the key element which prevents esophageal reflux. More recent research has highlighted the crural diaphragm (CD) as an additional critical component of the GERD barrier. We now know that the CD actively relaxes when the distal esophagus is distended and contracts when the stomach is distended. Crural myotomy in animal models increases esophageal acid exposure, highlighting the CD's vital role. There are also multiple physiological studies in patients with symptomatic hiatal hernia that demonstrate CD dysfunction is associated with GERD. Finally, computer models integrating physiological data predict that the CD and the LES each contribute roughly 50% to the GERD barrier. This more robust understanding has implications for future procedural management of GERD. Specifically, effective GERD management mandates repair of the CD and reinforcement of the LES. Given the high rate of hiatal hernia recurrences, it seems that novel antireflux procedures should target this essential component of the GERD barrier. Future research should focus on methods to maintain crural integrity, decrease hiatal hernia recurrence, and improve long-term competency of the GERD barrier.